Intravenous endothelin-1 and ventilatory sensitivity to hypoxia in humans. - Talbot, N; Balanos, G; Robbins, P; Dorrington, K (2008)
The effects of intravenous endothelin-1 (ET-1) on the ventilatory response to hypoxia were studied in healthy humans. Nine volunteers were each exposed twice to 4 hr eucapnic hypoxia. They received a continuous infusion of ET-1 during the ET-1 protocol and an infusion of saline during the control protocol. Plasma ET-1 levels and an index of ventilation were measured regularly. Hypoxia caused a rise in plasma ET-1 in the control protocol. Hypoxia also caused the index of ventilation to increase in both protocols, and this increase was greater in the ET-1 protocol than in the control protocol. These results are consistent with the hypothesis that ET-1 plays a role in controlling the ventilatory response to hypoxia in man.